Semiotics and Blackout Poetry at Lasalle College of the Arts - Zantides, Evripides (My University, 2025)
The workshop on Semiotics and Blackout Poetry investigates the intersection of written language, typography, and hierarchy of information through the practice of erasure-based poetic expression. Drawing on semiotics—the tstudy of signs and their meaning—it provides a framework for analyzing how written language, typography, and imagery contribute to the construction of meaning within both textual and graphic design layout. Blackout poetry, which entails the redaction of existing texts to uncover new narratives, operates as a methodological tool for the deconstruction and reconstruction of meaning. By selectively omitting words, participants engage in a semiotic process that destabilizes traditional notions of authorship, surfaces latent or personal narratives, and enables alternative readings of textual material to give birth to a poem. The workshop emphasizes the role of both presence and absence in the generation of meaning, foregrounding how erasure can function simultaneously as an aesthetic strategy and a political gesture. Through structured activities, participants will analyze the semiotic implications of their compositional choices, gaining insight into how visual, textual and hierarchical elements interact to produce layered interpretations. Additionally, they will explore the integration of illustration, image, or collage as extensions of their poetic text, further contributing to the overall communicative meaning and impact of their blackout poem.